Upaya Penurunan AKI Dan AKB Melalui Peningkatan Program Bangga Kencana Di Kabupaten Bantul - Chomariyati, Titik (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
Maternal Mortality Rate (MMR) is mortaity which happened during pregnancy or 42 days since the termination of pregnancy which are caused by complications during or after pregnancy. The major causes are bleeding, infections, high blood pressure during pregnancy, birth complications, and unsafe abortion. While Infant Mortality Rate (IMR) is the situation when the infant mortalityhappens <28 days after the birth which are caused by endegenous factors that is congenital factors and exogenous factors which is usually related with environment. Bangga Kencana is a Family Development, Population, and Family Planning Program, as a prevention of the issues related to basic service fulfillment on high Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), so it needs cooperation among many sectors to reduce the MMR and IMR. The main objective of this research is to know the contributions of Bangga Kencana Program to reduce MMR and IMR. The purpose of the study is to investigate the Bangga Kencana Program in reducing MMR and IMR. A qualitative method with a case study approach using longitudinal data from 2018-2020 is employed. The study identified it was important in collaborating with cross-sectoral and also Bangga Kencana Program socialization particularly 8 family functions. Implementation and habituation of 8 family functions in the community could reduce IMR and MMR in Bantul district.